The Trade Policy Review Mechanism: A new instrument with defects - Stefan Voigt (Intereconomics, 1990)
The “Trade Policy Review Mechanism” passed within the framework of the Uruguay Round is intended to increase the transparency of national trade policies and to improve adherence to the rules of GATT. The following article offers a first evaluation of the new instrument.
Keywords: 330; GATT